2011
DOI: 10.1016/j.crohns.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of babies exposed to azathioprine in utero and via breastfeeding

Abstract: Our study which reports the largest number of babies breastfed with exposure to AZA suggests that breastfeeding does not increase the risk of infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 20 publications
0
73
0
Order By: Relevance
“…Now different studies suggest that breastfeeding might be offered as an option to women on immunosuppressors such as prednisone, azathioprine and tacrolimus (14,15,40). The five infants in our study whose mothers opted for breastfeeding, when tested for lymphocyte immunophenotyping at 8 months of age, all had normal lymphocyte numbers, except for one who had borderline B cell numbers at that age, but normal levels when retested at 17 months.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Now different studies suggest that breastfeeding might be offered as an option to women on immunosuppressors such as prednisone, azathioprine and tacrolimus (14,15,40). The five infants in our study whose mothers opted for breastfeeding, when tested for lymphocyte immunophenotyping at 8 months of age, all had normal lymphocyte numbers, except for one who had borderline B cell numbers at that age, but normal levels when retested at 17 months.…”
Section: Discussionmentioning
confidence: 84%
“…However, in the beginning of 2011, due to new evidence that infants' immunosuppressor serum levels might be very low or undetectable (12)(13)(14)(15), the restriction not to breastfeed was taken in each case depending on discussion between the healthcare team and the mothers.…”
Section: Introductionmentioning
confidence: 99%
“…56 A long-term follow-up study of babies whose mothers breastfed for at least 6 months on azathioprine showed that there was no increased risk of infections and no impairment of physical or mental development of the children to at least 3.3 years (women who breastfed on AZA) versus 4.7 years (women who did not breastfeed on AZA). 57 Given these newer data, we recommend continuing AZA/6-MP while breastfeeding.…”
Section: Medications: Azathioprine and 6-mercaptopurinementioning
confidence: 97%
“…Studies have shown that infants are not at an increased risk of infections when breastfed by mothers exposed to thiopurines [70]. Overall, thiopurines are considered compatible with breastfeeding, although the long-term outcome of infants exposed to minute amounts during lactation are not known.…”
Section: Thiopurinesmentioning
confidence: 98%